Physical Acoustics in the Solid State - Lüthi, Bruno; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Suitable for researchers and graduate students in physics and material science, "Physical Acoustics in the Solid State" reviews the modern aspects in the field, including many experimental results, especially those involving ultrasonics. Practically all fields of solid-state physics are covered: metals, semiconductors, magnetism, superconductivity, different kinds of phase transitions, low-dimensional systems, and the quantum Hall effect. After a review of the relevant experimental techniques and an introduction to the theory of elasticity, emphasizing the symmetry aspects, applications in the various fields of condensed matter physics are presented. Also treated are Brillouin-scattering results and results from thermodynamic investigations, such as thermal expansion and specific heat.
Experimental Techniques -- Elasticity -- Thermodynamics and Phase Transitions -- Acoustic Waves in the Presence of Magnetic Ions -- Ultrasonics at Magnetic Phase Transitions -- Ultrasonics at Structural Transitions -- Metals and Semiconductors -- Unstable Moment Compounds -- Ultrasonics in Superconductors -- Coupling to Collective Excitations -- Ultrasonics in Low Dimensional Spin and Electronic Peierls-Systems -- Symmetry Effects with Sound Waves -- Ultrasonic Propagation in Tunneling Systems -- Conclusion and Outlook.
Keywords: Condensed matter; Acoustics; Optical materials; Electronic materials; Nanotechnology; Engineering; Condensed Matter Physics; Acoustics; Optical and Electronic Materials; Nanotechnology; Engineering, general